Pengaruh Komunikasi, Konflik Dan Stres Kerja Terhadap Produktivitas Kerja Karyawan Pada UD Harapan Jaya Kabupaten Kediri : (Studi Kasus Di UD Harapan Jaya Kabupaten Kediri) - Bima Sandhi Waluya; Aprilia Dian Evasari; Heru Sutapa (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This thesis research is motivated by a phenomenon of communication influence, conflict and work stress on employee performance productivity. This happened particular challenges for the management of human energy resources that exist in industry. They are required to change the HR management system by implementing protocols health. HR management managers changed their methods of control human resources owned by industry. Therefore, in facing the eraIn today's globalization, the quality of human resources is the main factor realizing the goals of a company. In companies, resource quality problems humans always receive special attention, because of their position in the role of resources Humans are highly expected in the development of the economy in Indonesia. The purpose of this research is to find out and explain partial influence of communication on employee work productivity at UD Harapan Jaya Kediri Regency, partial influence of conflict on work productivity employees at UD Harapan Jaya Kediri Regency, partial influence of work stress on employee work productivity at UD Harapan Jaya Kediri Regency, influence simultaneously communication, conflict and work stress on employee work productivity at UD Harapan Jaya, Kediri Regency.This research shows that: 1) Partially communication (X1) is not influence on employee work productivity at UD. Harapan Jaya Regency Kediri obtained a significant value of 0.052, which means a significant value of > 0.05. 2) Partially there is a significant effect of conflict (X2) on work productivity employees at UD. Harapan Jaya Kediri Regency obtained significant scoresof 0.004 which means the significant value is <0.05. 3) Partially, work stress (X3) is not influence on employee work productivity at UD. Harapan Jaya Regency Kediri obtained a significant value of 0.127, which means a significant value of > 0.05. 4) Simultaneously there is the influence of communication (X1), conflict (X2) and work stress (X3) on employee work (Y) on employee work productivity at UD. Jaya Hope Kediri Regency with a significant value of 0.005 means a significant value of <0.05